Development of The Brahma-Vihara Attitude Measurement Instrument Among Buddhist Adolescents - Anne Svasthi Gautami; Erika Yanti; Tegar Susanto; Rahmat Syah (Universitas Negeri Semarang, 2023)
Buddhism teaches four spiritual attitudes known as Brahma-Vihara: loving-kindness, compassion, empathetic joy, and equanimity. Applied in daily life, these attitudes can help teenagers develop good character traits such as empathy, tolerance, cooperation, and wisdom. This study aims to develop an instrument for measuring Brahma-Vihara attitudes among Buddhist adolescents in Tangerang Regency. The study used the Research and Development method with five stages of instrument development: literature study, instrument preparation, validation by experts, attitude assessment trial, and language instrument testing. A sample of 120 respondents was selected using purposive sampling technique, and the collected data were analyzed using confirmatory factor analysis and Cronbach's alpha reliability test. The results showed that the Brahma-Vihara attitude measurement instrument for adolescents in Tangerang Regency is valid and reliable for use in certain subjects. The instrument consists of 75 items with a five-point Likert scale and is divided into four dimensions of Brahma-Vihara attitudes, namely metta (loving-kindness), karuna (compassion), mudita (sympathetic joy), and upekkha (equanimity). This instrument can help facilitate Buddhists in understanding the noble qualities of Dhamma and provide benefits to the education world in developing attitude assessment instruments in certain subjects.